Life cycle assessment of an interlocking compressed earth brick system for green building construction - Nurul Shahadahtul Afizah Asman (2022)
Building construction significantly contributes to the carbon growth due to the high carbon emissions produced by buildings and their effects on climate change. Sustainable building products, materials, and construction techniques, namely green building materials selection is crucial to achieve sustainable construction. The type of building materials influences the carbon emissions of a construction project. Then contribute to the problem of pollution, where carbon dioxide is the primary pollutant that contributes to global warming's negative effects. Brick is a significant building material in the construction industry. Interlocking Compressed Earth Bricks (ICEB) has been introduced as an alternative low carbon building material replacing the conventional brick. The objective of this study is to determine the environmental impact of ICEB production using Life Cycle Assessment (LCA). Then to evaluate the environmental impacts and carbon footprint reduction of ICEB system with the conventional construction. This study also analyzes the hotspot of the energy used and C02 emission on material stages of residential building in Sabah. Finally, to develop a carbon calculator for ICEB manufacturing. In this study, quantification analysis using LCA is used to measure the environmental impact. The scope of this study cover cradle-to-gate system boundaries with 1 kg of functional unit and was conducted at the Interlocking Brick Teaching Factory located at the Faculty of Engineering, Universiti Malaysia Sabah. The embodied carbon was analyzed using the GaBi software. Meanwhile, the study of residential buildings involved the selected community housing project in Sabah evaluates using LCA for cradle-to-gate with lm2 of built-up area. The result shows that the embodied carbon of ICEB production is 0.202 kgC02eq and result on sensitivity analyses found that the GWP reduced (27%-51 %) with the cement content (10% and 15%). The implementation of ICEB in building construction contributes to carbon footprint reduction 34% from the conventional construction. ICEB is suitable to be used as a low carbon footprint building material where the conventional concrete and brickwork contribute to 75% (embodied energy) and 77% (embodied carbon) from the construction process. During hotspot identification for the material stage of building life cycle, concrete, brick, and steel are the major materials contributed to environmental impact of building construction. The adoption of the ICEB system in green building construction can lower the energy consumption (2.75 GJ/m2 of conventional, to a 1.3 GJ/m2), reduce the overall environmental impact (to 184 kgCOi/m2). This study develops a carbon footprint calculator which can evaluate the environmental impact of brick manufacturing in Sabah, Malaysia for product development. Sustainable materials (such as quarry dust) are calculated using the carbon calculator with various percentage of Portland cement replacement in ICEB mix design. The incorporation of the green materials improved the environmental impact. In general, implementation of sustainable materials in ICEB design mix production and construction can potentially reduce the greenhouse gases emission and hence maximize the carbon footprint reduction.